2008
DOI: 10.1021/nn800022d
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Investigations of the Thermodynamic Stability of Ba−C60 and K−C60 Compound Clusters

Abstract: A novel experimental set-up was used to study superstable (magic) Ba−C60 and K−C60 compound clusters. The most stable systems observed cannot be rationalized by simple electronic or by geometrical shell filling arguments. Annealing the clusters past the temperature necessary for the fragmentation of the initial metastable clusters formed at the source reveals information about their thermodynamic stability. Higher temperatures yield larger species, suggesting that similar experiments may be used to rationally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 61 publications
4
31
0
Order By: Relevance
“…In other words, the adatoms decorate a hemisphere of C 60 [11,12,37]. For C 60 Na 6 and C 60 K 6 , on the other hand, it is found that adatoms preferentially bind to hexagonal sites and stay away from each other as far as possible [8,36,37,41] 5 .…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In other words, the adatoms decorate a hemisphere of C 60 [11,12,37]. For C 60 Na 6 and C 60 K 6 , on the other hand, it is found that adatoms preferentially bind to hexagonal sites and stay away from each other as far as possible [8,36,37,41] 5 .…”
Section: Discussionmentioning
confidence: 95%
“…Li + prefers triangular interstitial sites whereas Na + and K + prefer tetrahedral sites. Zurek et al [8] find that the adatoms in (C 60 ) 2 K 4 reside in the groove between the two C 60 . Apparently the enhanced adsorption energy at groove sites [45] outweighs the tendency for ions to spread out uniformly due to Coulomb repulsion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations